The Role of Agglomeration and Technology in Shaping Firm's Strategy and Organization - Giulio Cainelli; Donato Iacobucci (European Regional Science Association (ERSA), 2006)
Vertical integration, i.e. the control of activities along the production chain, is a fundamental issue for understanding firms' strategic choices and production organization. In this paper we analyze the determinants of vertical integration in Italian manufacturing firms testing some hypotheses drawn from the transaction cost economics (TCE) and the property rights theory (PRT). Specifically, we focus on the role played by structural variables, such as spatial agglomeration and technology. While the role of technology in influencing vertical integration has been already investigated, the impact of spatial agglomeration is a novel contribution of this paper. The PRT makes the prediction that greater technology intensity of producers should be associated with greater vertical integration while greater technology intensity of suppliers should be associated with less vertical integration. The TCE makes the opposite hypothesis as the technology intensity of suppliers is associated with investment specificity, thus inducing vertical integration. As far as spatial agglomeration is concerned PRT makes the prediction that spatial proximity encourages vertical integration by raising the threat of knowledge appropriation by competitors. This effect is positive in high tech sectors while should be negligeable in low tech sectors. On the contrary TCE predicts a negative relationship between spatial agglomeration and vertical integration due to the reduction of opportunism within spatial clusters, such as industrial districts. In the empirical part of the paper we take advantage of a large data set on Italian business groups referring to 2001 which allow us to identify the production activities controlled by the same owner. In addition, using the Italian input-output table we are able to assess when these activities can be considered as vertical integration. Technology intensity is captured by the R&D expenditure while spatial agglomeration is captured by the belonging of firms to industrial districts as defined according to the Sforzi-ISTAT procedure. On the basis of these data we test different econometric specifications to detect the statistical relevance of technology, spatial agglomeration and their interaction in explaining firms' vertical integration.
Keywords: 330